PENGARUH MOTIVASI KERJA KARYAWAN TERHADAP KINERJA KARYAWAN DI RUMAH SAKIT UMUM DAERAH WONOSARI KABUPATEN GUNUNGKIDUL D.I. YOGYAKARTA - Wilis Fahlefi; Sulistriani Sulistriani (ALBAMA: JURNAL BISNIS ADMINISTRASI DAN MANAJEMEN, 2021)
The purpose of this study was to determine the effect of motivation on employee performance at the Wonosari Regional General Hospital, Yogyakarta Special Region. The population taken is all employees of the Wonosari Regional General Hospital, totaling 50 people as a sample. Data was collected by distributing questionnaires to respondents. The collection technique using SPSS.17. based on the results of the study it was stated that the motivation variable had a positive and significant effect on employee performance having a significant value of 0.000 <0.05.